2013
DOI: 10.1186/2191-219x-3-81
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein isolation in patients with paroxysmal atrial fibrillation is associated with regional cardiac sympathetic denervation

Abstract: BackgroundCircumferential pulmonary vein isolation (PVI) is the cornerstone of the current state-of-the-art management of atrial fibrillation (AF). However, the precise mechanisms behind AF relapses post PVI are still unknown. Since the activity of the autonomous nervous system is crucial in triggering paroxysmal AF, we hypothesized that PVI is associated with changes of cardiac sympathetic activity.MethodsSixteen patients with paroxysmal AF underwent cardiac iodine-123-meta-iodobenzylguanidine (123I-mIBG) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
0
23
0
4
Order By: Relevance
“…Thus, to determine the indications for the procedure of "MAZE III" expedient to EPS on technology developed before the intervention with the assessment of the functional state of the sinoatrial node. When it is appropriate we need to assess the initial severity of the patient's condition and the effect on it of atrial fibrillation [21][22][23][24][25]. If AF has no pronounced negative effect on the hemodynamics of the patient, it makes sense to restrict the atrial appendages off by their resection and suturing, in addition to the main stage of the operation to reduce the risk of thromboembolic complications.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Thus, to determine the indications for the procedure of "MAZE III" expedient to EPS on technology developed before the intervention with the assessment of the functional state of the sinoatrial node. When it is appropriate we need to assess the initial severity of the patient's condition and the effect on it of atrial fibrillation [21][22][23][24][25]. If AF has no pronounced negative effect on the hemodynamics of the patient, it makes sense to restrict the atrial appendages off by their resection and suturing, in addition to the main stage of the operation to reduce the risk of thromboembolic complications.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Arimoto et al performed 123 I-mIBG on the day prior to and 5 days post-ablation in 20 AF patients [1], while Wenning et al performed regional analysis and reported a newly emerging deficit in 123 I-mIBG uptake in left ventricle 1 month post-ablation [9]. In these studies, H/M during the early and delayed phases and WR did not markedly change post-ablation.…”
Section: Previous Reportsmentioning
confidence: 95%
“…[1][2][3] The adrenergic part of CANS can be evaluated with I-123-metaiodobenzylguanidine (MIBG), which is a norepinephrine analog and a tracer for sympathetic neuron integrity and function. 4 MIBG imaging has been performed to assess patients with AF, for: (1) the prognosis of patients with paroxysmal atrial fibrillation (PAF) 5,6 ; (2) the prediction of outcome of catheter ablation of AF 7,8 ; and (3) evaluation of denervation/ renervation after AF ablation. 8,9 In patients with PAF and without structural heart disease, CAS abnormality defined as reduced H/M ratio from planar MIBG delayed imaging was a predictor of vascular events (myocardial infarction, stroke, or heart failure) during a mean of 4.5 years follow-up.…”
mentioning
confidence: 99%